Analisis Berbasis Tinjauan Literatur Tentang Kontribusi Manajemen Risiko Terhadap Kinerja Organisasi - Erta Bayu Novriadi; Setiawati, Merika (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study aims to examine the impact of risk management implementation in an organisation. This study uses literature analysis from various sources used in the study of the topics discussed in this research article. The results of this study from various reviewed and analysed literature show that risk management in practice plays a major contribution to the reliability of an organisation's performance in achieving its objectives. The application of risk management concepts, which include the stages of risk identification to risk monitoring, is crucial for organisations in guiding their existing performance. Oganisations that want to achieve good performance in their organisations must apply risk management in the sustainability of the organisation.